2022
DOI: 10.1007/s40299-022-00645-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Mobile-Game-Based Collaborative Prewriting on EFL Students’ Individual Writing in Student-Centered Class Context

Abstract: To motivate learners to engage in writing courses and help to improve their writing performance, a mobile-game-based collaborative prewriting approach was proposed in this study. A quasi-experiment was implemented by recruiting two classes of non-English major students from a university in northeastern China. Class 1 learned to write under the guidance of the mobile-gamebased collaborative prewriting method, while Class 2 in the conventional teacher-centered approach. Their writing performance was measured to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Similarly, Sarvary et al (2022) found that online learning through technological devices and in-person courses provide opportunities for improving studentcentered Biology laboratory instruction. Moreover, Turdieva and Olimov (2021) and Wang and Song (2022) disclosed that games technology is an innovative type of studentcentered learning, and provided significant contribution in developing students' autonomous learning. From these previous studies we are well informed that technology possesses crucial role in fostering student-centered learning in various contexts of education.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sarvary et al (2022) found that online learning through technological devices and in-person courses provide opportunities for improving studentcentered Biology laboratory instruction. Moreover, Turdieva and Olimov (2021) and Wang and Song (2022) disclosed that games technology is an innovative type of studentcentered learning, and provided significant contribution in developing students' autonomous learning. From these previous studies we are well informed that technology possesses crucial role in fostering student-centered learning in various contexts of education.…”
Section: Introductionmentioning
confidence: 99%